The Knowledge and Perception of Hand Hygiene Among Health Care Workers in Clinical Settings in Khartoum State - Sudan - M. BaderAldeen, Ragda; I. Kheder, Salah (Journal of Medical Informatics and Decision Making, 2020)
Objective This study conducted to assess health care practitioners’ knowledge and perceptions of hand hygiene among health professional working in clinical settings in Khartoum State - Sudan. with the specific objective of determining the association between their stance on hand hygiene and the general demographic characteristics of these health-care professionals.   Methodology This is a cross-sectional study conducted between July and November 2017 using a modified form of WHO questionnaire for knowledge and perception that was included 22 items was sent online to health care workers via social media. The data obtained entered and analyzed by SPSS version 24. Chi-square and test of independence were used as a test of significance. A p-value of < 0.05 was considered statistically significant for all purposes.  Result 437 hospital staff were responded to the questionnaire. (99.3%) was found to have good knowledge. 197(45.2%) had good perception and 239(54.8%) had fair perception. Formal hand hygiene training was found to have no association with knowledge levels of hand hygiene, but the fair perception was higher in the respondents who didn’t receive formal training.  Conclusion The present study highlights the hand hygiene knowledge and perception. Most health care workers were found to have good knowledge, and the majority was found to have a fair perception. Formal hand hygiene training courses were found to have no association with knowledge but it may be reflected in practice. The importance of training sessions regarding hand hygiene was noticed in the perception level.
Keywords: Hand-hygiene knowledge; Hand hygiene perception; Hand wash; Hand rub; Sudan